O19 Sexual partnership patterns and sexually transmitted infections in HIV positive men who have sex with men: implications for partner notification. (23rd May 2012) - Wayal, S; Cassell, J A; Edwards, S; Hart, G
Abstract : Aims: It is essential to understand the implications of sexual partnerships, sexual networks and type of sexually transmitted infections (STIs) on partner notification to maximise its effectiveness. We examined the relationship of these factors with HIV+ve men who have sex with men's (MSM) attitudes towards partner notification. Methods: 24 purposively selected men participated in semi-structured interviews (May 2010–February 2011). Piloted vignettes about different types of STIs diagnosis and sexual partners were used to facilitate discussion. Framework analysis was conducted. Results: Men perceived the personal and public health benefits of HIV/STIs notification. However, HIV was perceived as a "fatal illness" and partner notification as "imperative" to facilitate partners' access to antiretroviral treatment. Some men preferred immediate HIV partner notification to allow post-exposure prophylaxis; others preferred to wait due to their own emotional burden of HIV diagnosis. Men perceived HIV notification with greater fear of stigma and "blame culture" than STIs notification. Concerns regarding breach of confidentiality and long-term relationships were perceived barriers to HIV partner notification, while clinic advice and support was favoured. Men who intentionally engaged in bareback sex perceived STIs partner notification as "the norm". However, some men emphasised their and partners' "personal responsibility" to test for STIs regularly. Men favoured notifying a boyfriend and regular partners personally, especially for non-curable STIs like Hepatitis C (HCV). However, fear of being blamed or blaming group/casual sex partners, especially for HCV, were barriers to STIs notification. Provider-led or anonymous-notification methods were preferred in such cases. Conclusions: HIV+ve MSM should be offered clinic support for patient-led HIV notification, provider-led methods for HCV notification, and notifying group/casual sex partners to improve partner notification.